2011
DOI: 10.1007/s13280-011-0192-y
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bathymetric Data in Society and Science: A Review from the Baltic Sea

Abstract: Bathymetry, the underwater topography, is a fundamental property of oceans, seas, and lakes. As such it is important for a wide range of applications, like physical oceanography, marine geology, geophysics and biology or the administration of marine resources. The exact requirements users may have regarding bathymetric data are, however, unclear. Here, the results of a questionnaire survey and a literature review are presented, concerning the use of Baltic Sea bathymetric data in research and for societal need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Characteristic seafloor bedforms, both erosional and depositional, have long been used to provide information on bottom current velocity and flow direction in studies of both modern and past oceanographic conditions (Hollister and Heezen, 1972;Kenyon and Belderson, 1973). With highresolution multibeam bathymetry acquired with surface ves-sels in relatively shallow waters such as in the Baltic Sea, we are able to make use of bedforms scaling from a few decimetres in size at the very best or, more commonly, from a few metres.…”
Section: Bathymetric Sills and Seafloor Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic seafloor bedforms, both erosional and depositional, have long been used to provide information on bottom current velocity and flow direction in studies of both modern and past oceanographic conditions (Hollister and Heezen, 1972;Kenyon and Belderson, 1973). With highresolution multibeam bathymetry acquired with surface ves-sels in relatively shallow waters such as in the Baltic Sea, we are able to make use of bedforms scaling from a few decimetres in size at the very best or, more commonly, from a few metres.…”
Section: Bathymetric Sills and Seafloor Processesmentioning
confidence: 99%
“…Bendtsen et al, 2009;Gogina and Zettler, 2010;Omstedt et al, 2014;Stigebrandt, 2001; Rolff and Elfwing, 2015), internal mixing in deep waters (Lappe and Umlauf, 2016;Nohr and Gustafsson, 2009), and bottom habitats (Kaskela and Kotilainen, 2017) -are necessary input parameters to many physical and environmental studies. Bathymetry is needed in almost all fields of marine science, preferably compiled into a digital bathymetric model (DBM) suitable for analyses and/or as a framework in numerical models (Hell et al, 2012). A DBM is a digital terrain model (DTM; see Li, 2004) where the terrain specifically represents the seafloor, commonly formatted as a regular grid with depths assigned to the grid cells.…”
Section: Introductionmentioning
confidence: 99%
“…For high‐resolution bathymetry see Hell et al . () and Baltic Sea Bathymetry Database (). B. Close‐up of the study area where the seismic profiles included in the database used for this study are marked by lines and core locations are shown as grey stars.…”
mentioning
confidence: 99%
“…The problems of the currently available bathymetry datasets for small government departments relate to a lack of spatial resolution, spatial coverage [21], and the temporal frequency of repeatable surveys. SBES, MBES, and LiDAR models capture the spatial resolution required, but not always at the spatial coverage needed and at reasonable costs.…”
Section: Introductionmentioning
confidence: 99%